Saan na po ang Olongapon ; Ad ban ; Leap of faith [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles the situation of Olongapo residents after the pull-out of American military base; COMELEC ban on political advertisements; Kenny Loggins concert in Manila and interview about his philosophy and inspiration in life.
Saan na po ang Olongapon (15 min.) -- Ad ban (13 min.) -- Leap of faith (21 min.)
VHS.
Keywords: Loggins, Kenny -- Interviews; Olongapo City -- Economic conditions; Advertising, Political -- Philippines